ANALISIS QUALITY OF SERVICE JARINGAN INTERNET PT. JAWA POS NATIONAL NETWORK MEDIALINK PONTIANAK - ., Nur Azizah (Fakultas Teknik, 2016)
ABSTRACT- One of internet network services that often are accessed by people is streaming and downloading video. PT. Jawa Pos National Network Medialink is a company engages in services of technology based on internet network to public in Pontianak generally. The company that has running in providing the internet network, it gives the best quality network is an obligation. The investigation was conducted in PT. JPNN Medialink Pontianak by 6 clients that the test was held twice to each client in order to obtain some comparative research data. Data result of QoS parameter testing for 6 clients was 68,554% for throughput value with index value was 3 in good category, packet loss value was 0% with index value was 4 in very good category, delay value was 13,666 ms with index value was 4 in very good category, jitter value was 13,664 ms with index value is 3 in good category, internet access speed value consisted of download speed was 68,027% with index value was 3 in good category and upload speed was 48,943% with index value was 2 in medium category. And then, the average index to TIPHON for all QoS parameter was 3,4763 with satisfied category. Some factors that cause the QoS value declined were the using resources, number of users that accessed on 1 client location, condition of network device, weather, distance and some obstacles. Keywords : Quality of Service (QoS), Throughput, Packet Loss, Delay, Jitter, Internet Access Speed.